2014
DOI: 10.1002/hbm.22689
|View full text |Cite
|
Sign up to set email alerts
|

Toward systems neuroscience in mild cognitive impairment and Alzheimer's disease: A meta‐analysis of 75 fMRI studies

Abstract: Most of the previous task functional magnetic resonance imaging (fMRI) studies found abnormalities in distributed brain regions in mild cognitive impairment (MCI) and Alzheimer's disease (AD), and few studies investigated the brain network dysfunction from the system level. In this meta-analysis, we aimed to examine brain network dysfunction in MCI and AD. We systematically searched task-based fMRI studies in MCI and AD published between January 1990 and January 2014. Activation likelihood estimation meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
129
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 127 publications
(102 reference statements)
23
129
2
Order By: Relevance
“…This finding is in line with previous meta-analyses centered on the DMN [21,22], and a recent study published after we completed our analysis [23]. DMN deterioration appears robust to the choice of analytical approaches, as previous meta-analyses largely included studies measuring regional homogeneity and amplitude of low-frequency fluctuation.…”
Section: Late-onset Adsupporting
confidence: 90%
“…This finding is in line with previous meta-analyses centered on the DMN [21,22], and a recent study published after we completed our analysis [23]. DMN deterioration appears robust to the choice of analytical approaches, as previous meta-analyses largely included studies measuring regional homogeneity and amplitude of low-frequency fluctuation.…”
Section: Late-onset Adsupporting
confidence: 90%
“…For example, alexithymia was associated with apathy and companion's distress in patients with neurodegenerative diseases [77] and neurodegenerative diseases implicated FPN and DMN atrophy [78]. While MBB effects on FPN, VAN, and DMN cortical networks remain to be tested in the future, we hope our presentation of MBB as practice and the AGIR model as neuroscience-informed theory will be useful in stimulating readers to continue to search for resolutions (or dissolutions) for dysfunctional problems originating in the counter-productive embodiment of identity-grasping fallacy.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, reduced resting-state activity was also found in the PCC, right angular gyrus, right parahippocampal gyrus and left fusiform gyrus that were not reported in the previous ALE study. 12 Importantly, the absence of reduced restingstate activity in these regions in the previous ALE study included a heterogeneous sample of MCI patients (that is, aMCI and svMCI), suggesting that the two subtypes of MCI may possess distinct pathophysiological characteristics. In fact, increases in restingstate activity in the PCC have been reported in patients with svMCI.…”
Section: Discussionmentioning
confidence: 53%
“…12 Indeed, a previous study that reported a similar resting-state hypoactivity in the medial frontal gyrus was conducted in svMCI patients compared with controls, 13 and the study was also included in the previous ALE meta-analysis. We did not, however, observe any significant hypoactivity in these regions in aMCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation